Genome-Wide Integrated Analysis Revealed Functions of lncRNA–miRNA–mRNA Interaction in Growth of Intermuscular Bones in Megalobrama amblycephala - Chen, Yulong; Wan, Shiming; Li, Qing; Dong, Xiaoru; Diao, Jinghan; Liao, Qing; Wang, Gui-Ying; Gao, Ze-Xia (Frontiers in Cell and Developmental Biology, 2021)
Intermuscular bone (IB) occurs in the myosepta of teleosts. Its existence has an adverse influence on the edible and economic value of fish, especially for aquaculture species belonging to Cypriniformes. The growth mechanism of IBs is quite lacking. In this study, we firstly used single molecular real-time sequencing (SMRT) technology to improve the draft genome annotation and full characterization of the transcriptome for one typical aquaculture species, blunt snout bream (Megalobrama amblycephala). The long non-coding RNA (lncRNA), microRNA (miRNA), and messenger RNA (mRNA) expression profiles in two IB growth stages (1 and 3 years old) were compared through transcriptome and degradome analyses. A total of 126 miRNAs, 403 mRNAs, and 353 lncRNAs were found to be differentially expressed between the two stages. Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis revealed that the significantly upregulated map2k6 and cytc in the MAPK/p53 signaling pathway and the significantly downregulated lama3 and thbs4b in the extracellular matrix (ECM)–receptor pathway may play a key regulatory role in IB growth. Bioinformatics analysis subsequently revealed 14 competing endogenous RNA (ceRNA) pairs related to the growth of IBs, consisting of 10 lncRNAs, 7 miRNAs, and 10 mRNAs. Of these, dre-miR-24b-3p and dre-miR-193b-3p are core regulatory factors interacting with four lncRNAs and three mRNAs, the interaction mechanism of which was also revealed by subsequent experiments at the cellular level. In conclusion, our data showed that IBs had higher activity of cell apoptosis and lower mineralization activity in IB_III compared to IB_I via interaction of MAPK/p53 and ECM–receptor signaling pathways. The downregulated zip1 interacted with miR-24a-3p and lnc017705, decreased osteoblast differentiation and Ca2+ deposition in the IB_III stage. Our identified functional mRNAs, lncRNAs, and miRNAs provide a data basis for in-depth elucidation of the growth mechanism of teleost IB.